INVOLVEMENT ARACHIDONIC ACID CASCADE IN MEMORY DEFICIT BY KRATOM (Mitragyna speciosa) IN MALE WISTAR RATS - Ramadhani, Chelsea Aulia; Anggadiredja, Kusnandar (School of Pharmacy Institut Teknologi Bandung, 2024)
Kratom (Mitragyna speciosa) is a plant that is widely found in Southeast Asia particularly, in Indonesia. Mitragynine, which was the main alkaloid of kratom, has been reported associated with addictiveness and memory impairment in animal studies. However, the mechanism of memory impairment is still unclear. In the present study, we investigated the involvement of the arachidonic acid cascade in memory impairment caused by kratom. Male Wistar rats were divided into seven groups, namely vehicle (CMC Na 0.5%; oral), kratom ethanolic extract (50, 100 and 200 mg/Kg; oral (p.o)), and the group given Diclofenac Sodium (5 mg /Kg; Intraperitonial (i.p)) 30 mins before administration of kratom ethanolic extract (50, 100 and 200 mg/Kg; oral) for 14 days. Memory impairment was carried out using a spatial memory test on days 10-16 using the Morris Water Maze and a working memory test using the Y Maze on the 17th day. Kratom administration was shown to impair spatial memory and working memory when compared with the vehicle group (P<0.05). Diclofenac sodium prevents spatial memory and working memory impairment due to Kratom when compared to the group administered by kratom monotherapy at the equivalent dose (P<0.05). In this study, it was found that there was involvement of the arachidonic acid cascade in memory impairment by kratom.